Enhancing Islamic Education Institutions’ Quality to Capture Public Interest (A Multi-Site Study at MTs Darul Hikmah and MTs Mamba’ul Ulum Tulungagung) - Indrioko, Erwin (Didaktika Religia, 2022)
Science development of modern knowledge brings a signiﬁcant impact on Islamic education. On one side, must capably compete with the education public who have together high and on the other hand, not let go of existence as a moral basis. Therefore, this research seeks to uncover effort enhancement together as well as a strategy for creating interest Public through multi-site research in two institutions of Islamic education. Using qualitative data excavated description through technique Interview deep, observation participatory and documentation to prayer institution namely MTs Darul Hikmah Tulungagung and MTs Mamba'ul Ulum Tulungagung. Informant look for sources from the head of the madrasa, Deputy Head of Public Relations, Deputy Head of Guarantee quality, teachers, and guardians of students. The result of this research shows that strategy in attracting community interest held at MTs Darul Hikmah Tulungagung and MTs Mamba'ul Ulum Tulungagung is implementing system total quality management, where the second institution by sustainable increase together power educators, facilities and infrastructure, management education, learning process, competence graduate, evaluation education and financing. To increase public interest, MTs Darul Hikmah Tulungagung and MTs Mamba'ul Ulum Tulungagung publish some self image through social media and mass media. This publication aims to know the public thought about the existence of a madrasa. Efforts to build the quality of the institution on an ongoing basis have implications for the increasing number of new student applicants every year.